Monitoring the follow-up of autoimmune chronic atrophic gastritis using parietal cell antibodies and markers of gastric function - Maria Piera Panozzo; Antonio Antico; Nicola Bizzaro (Journal of Translational Autoimmunity)
Increased interest in the pathogenesis and the evolution of autoimmune chronic atrophic gastritis (A-CAG) has led to the search for serological markers that can be used to detect changes in the gastric mucosa at an early stage and to monitor the course of the disease. Parietal cell autoantibodies have been proposed as suitable immunological markers of atrophic damage, as they can be detected in the serum when symptoms of gastritis are not yet present. However, the utility of measuring only the level of parietal cell autoantibodies in the follow-up of A-CAG does not appear to suffice. Recent evidence has suggested that, in monitoring A-CAG, parietal cell antibodies should be associated with an evaluation of gastric function through biochemical and hormonal tests, such as pepsinogens and gastrin 17. This integrated approach will allow for the more effective real-time monitoring of the state of the gastric mucosa. As A-CAG is a progressive disorder associated with an increased risk of gastric cancer and neuroendocrine tumors, the precise follow-up of patients with gastric atrophy needs to be better defined. Further longitudinal studies in large cohorts must be performed with long-term follow-up.